Effects of e-book formats on undergraduates’ Learning of statistics - Lim, Bibiana Chiu Yiong (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Universities are trending towards electronic books (e-books) as instructional materials, displacing the traditional printed books. However, there is an incomplete body of knowledge on which preferred presentation formats in e-books by students, particularly in statistics learning. As a result, this study was conducted to investigate the effects of three different e-book formats, namely, text and static image (T&S), text and animation (T&A), and text and multimedia (T&M) e-book formats in a first year undergraduate statistics unit. The e-books were designed according to Baddeley and Hitch’s (1974) information processing theory, Paivio’s (1986) dual-coding theory and Mayer’s (2001) multimedia principles. The Waterfall model was applied as a guide to develop and deploy the e-books into website. The e-book was based on an introductory statistics unit under the Bachelor of Commerce program in Swinburne University of Technology (Sarawak campus) in Malaysia. The experiment also assessed whether a relationship exists between the statistics anxiety, individual’s learning style as experience, in which may influence the academic achievement. A quasi-experimental design was adopted where the study was conducted using Non-Equivalent Group, Posttest-Only Design. The participants were divided into three tutorial groups, with control group assigned with T&S e-book. 89 participants responded and completed all the treatments over 12 weeks. Data were gathered employing questionnaires using both quantitative and qualitative techniques. Results indicated that the T&S e-book format showed higher cognitive load and the participants obtained lower scores in examinations compared to T&A and T&M e-book formats, but no significant difference was found between the T&A and T&M e-book formats. Both self-efficacy and statistics anxiety was found to have no effect on any of the e-book format. Results from hierarchical multiple regression analysis revealed that gender, computer use experience and learning styles imposed no significant effect on participants’ level of cognitive load, level of self-efficacy, level of statistics anxiety and achievement within the control and treatment groups. Cognitive load was found to have a weak negative relationship with achievement. In addition, there was an inverse relationship between selfefficacy level and statistics anxiety. Research into the preferred e-book format and effective way of presenting information in e-book imparts instructors and e-book course designer with information to enhance students’ learning.